Ciclo project “strengthening the circular economy skills of the eu labour services” - circular economy in Portugal - Barbas, Maria Potes (2020)
The CICLO project “Strengthening the circular economy skills of the EU Labour Services” is an Erasmus + KA2 that aims to improve and multiply the opportunities for improvement and requalification of long-term and low-skilled unemployed workers, in the field of evolution the circular economy market, through innovative vocational education and training (VET) tools and pedagogies, accompanied by skills assessment, recognition and validation methods. To that end, the CICLO project envisages the development of an interactive labor market and online skills ecosystem, geared to the needs of the circular economy, providing a training package for employed and unemployed people in order to equip them with basic skills related to recycling, opportunities for management, reuse and remanufacturing and service development (instead of products). The project is divided into five different intellectual outputs, comprising the following products: Cos Ecosystem of Circular Economy Skills and Methodological Framework; Cur CICLO curriculum and VET toolbox for key skills acquisition resources; Platform Multifunctional and Interactive Platform; Assessment Skills assessment, validation and recognition tools and Package Adaptation and policy package. Through these five phases, the project will offer a course of action to combat low levels of circular economy skills among long-term unemployed and low-skilled workers, while enabling unemployed workers and people to become creators of their own career through the economy market Circular. The project will also maximize your employability opportunities, enhance the development of critical media literacy skills and competences in VET and provide innovative VET teaching methods, best practice guidelines and strategies for using digital tools and innovative learning environments. The project is managed by a consortium of 8 European partners, covering a wide range of knowledge related to the scope and objectives of the project, also having a pan-European scope in its activities, with the Polytechnic Institute of Santarém being one of these partners. With this article, we intend, through the impulse of the project, to give Portugal's vision on the great theme of the CICLO project, the Circular Economy. We will focus on four topics: what is the Circular Economy, strategies adopted by Portugal, surrounding policies and business examples that have adopted this model.